2010
DOI: 10.1590/s0103-84782010005000116
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade de grãos da soja em função do manejo de herbicida e fungicidas

Abstract: RESUMO Com a introdução da soja resistente ao glifosato, ocorreu mudança no manejo da cultura, principalmente com relação ao manejo das plantas invasoras. Este trabalho foi desenvolvido com o objetivo de avaliar os efeitos da aplicação ('NK Mireya 4.2 RR', 'Fundacep 55 RR', 'NK Mágica 7.3 RR' and 'A 8100 RG')

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…The varieties Ativa and 5909 shared the highest TSW at both sites (Table 6). TSW is one of the components driving soybean yield (Ludwing et al 2010;Thomas and Costa 2010); however, no significant relationship was found between TSW and seed yield for varieties investigated (Table 5). There is a variety-dependent relative contribution of each yield component on seed yield.…”
Section: Soybean Seed Yield and Yield Componentsmentioning
confidence: 97%
“…The varieties Ativa and 5909 shared the highest TSW at both sites (Table 6). TSW is one of the components driving soybean yield (Ludwing et al 2010;Thomas and Costa 2010); however, no significant relationship was found between TSW and seed yield for varieties investigated (Table 5). There is a variety-dependent relative contribution of each yield component on seed yield.…”
Section: Soybean Seed Yield and Yield Componentsmentioning
confidence: 97%
“…Alternativa que vem sendo bastante estudada recentemente no Brasil e no mundo, no âmbito de melhorar o desempenho de sementes e plantas no campo, é a utilização de aminoácidos em diferentes culturas e formas de aplicação, a fim de promover o crescimento de plantas e melhorar a produtividade e qualidade dos produtos colhidos , BETTONI et al, 2013, HAMMAD & ALI, 2014WANG et al, 2014;MONDAL et al, 2015). No mercado, existe uma vasta gama de produtos disponíveis a serem utilizados em tratamento de sementes, e a disponibilidade de produtos contendo aminoácidos em sua composição é crescente (LUDWIG et al, 2010). Os aminoácidos são ácidos orgânicos associados a um ou mais grupamentos amina, com a função principal de constituir as proteínas e serem precursores de várias substâncias que regulam o metabolismo vegetal.…”
Section: Introductionunclassified